Gene Expression Profiling and Fine Mapping Identifies a Gibberellin 2-Oxidase Gene Co-segregating With the Dominant Dwarfing Gene Ddw1 in Rye (Secale cereale L.) - Braun, Eva-Maria; Tsvetkova, Natalia; Rotter, Björn; Siekmann, Dörthe; Schwefel, Konrad; Krezdorn, Nicolas; Plieske, Jörg; Winter, Peter; Melz, Gilbert; Voylokov, Anatoly V.; Hackauf, Bernd (Frontiers in Plant Science, 2019)
The gibberellin (GA)-sensitive dwarfing gene Ddw1 provides an opportunity to genetically reduce plant height in rye. Genetic analysis in a population of recombinant inbred lines confirmed a monogenetic dominant inheritance of Ddw1. Significant phenotypic differences in PH between homo- and heterozygotic genotypes indicate an incomplete dominance of Ddw1. De novo transcriptome sequencing of Ddw1 mutant as well as tall genotypes resulted in 113,547 contigs with an average length of 318 bp covering 36.18 Mbp rye DNA. A hierarchical cluster analysis based on individual groups of rye homologs of functionally characterized rice genes controlling morphological or physiological traits including plant height, flowering time and source activity identified the gene expression profile of stems at the begin of heading to most comprehensively mirror effects of Ddw1. Genome-wide expression profiling identified 186 transcripts differentially expressed between semi-dwarf and tall genotypes in stems. In total, 29 novel markers have been established and mapped to a 27.2 cM segment in the distal part of the long arm of chromosome 5R. Ddw1 could be mapped within a 0.4 cM interval co-segregating with a marker representing the C20-GA2-oxidase gene ScGA2ox12, that is up-regulated in stems of Ddw1 genotypes. The increased expression of ScGA2ox12 observed in semi-dwarf rye as well as structural alterations in transcript sequences associated with the ScGA2ox12 gene implicate, that Ddw1 is a dominant gain-of-function mutant. Integration of the target interval in the wheat reference genome sequence indicated perfect micro-colinearity between the Ddw1 locus and a 831 kb segment on chromosome 5A, which resides inside of a 11.21 Mb interval carrying the GA-sensitive dwarfing gene Rht12 in wheat . The potential of Ddw1 as a breeder’s option to improve lodging tolerance in rye is discussed.